Preventing pressure injuries in the emergency department: Current evidence and practice considerations. Issue 3 (27th February 2019) - Santamaria, Nick; Creehan, Sue; Fletcher, Jacqui; Alves, Paulo; Gefen, Amit
Abstract : The emergency department (ED) is at the front line of hospital pressure injury (PI) prevention, yet ED clinicians must balance many competing clinical priorities in the care of seriously ill patients. This paper presents the current biomechanical and clinical evidence and management considerations to assist EDs to continue to develop and implement evidence‐based PI prevention protocols for the high‐risk emergency/trauma patient. The prevention of hospital‐acquired pressure injuries has received significant focus internationally over many years because of the additional burden that these injuries place on the patient, the additional costs and impact to the efficiency of the hospital, and the potential for litigation. The development of a PI is the result of a complex number of biomechanical, physiological, and environmental interactions. Our understanding of the interaction of these factors has improved significantly over the past 10 years. We have demonstrated that large reductions in PI incidence rates can be achieved in critical care and general hospital wards through the application of advanced evidence‐based prevention protocols and believe that further improvement can be achieved through the application of these approaches in the ED.